PTU-171 Buried Barrett'S Dysplasia ('Bbad') Study: Results from a long Term follow up Study of Barrett'S Neoplasia Cohort. (4th June 2013) - Tholoor, S; Bhattacharyya, R; Tsagkournis, O; Basford, P; Bhandari, P
Abstract : Introduction: Buried Barrett's' or Subsquamous intestinal metaplasia (SSIM) refers to glands which are 'buried' underneath the squamous epithelium. High dose acid suppressive therapy and lack of acid exposure can result in squamous re-epithelialisation over the Barrett's mucosa. Buried Barrett's can pose significant diagnostic and surveillence challenges. Data on the prevalance of Buried Barrett's in endoscopic therapy naïve patients is limited. Like wise there is limted data on the prevalance of Buried Barrett's in patients following EMR. We aim to study and compare the prevalence of Buried Barrett's in these two groups of patients. Methods: Inclusion Criteria: Patients with Barrett's referred for endoscopic treatment between June 06 and June 12 Patients with Barrett's dysplasia following EMR procedure. Biopsy: Biopsies were first obtained from any suspicious looking area. Following this, biopsies were then obtained from the neosquamous area. Finally, random biopsies were obtained. These were sent in separate cassettes. Histopathology was reported by two independent GI pathologists and was prospectively recorded on a central pathology database. Buried Barrett's was defined as any metaplastic or glandular tissue beneath the squamous epithelium. Pathology specimens were reported by 2 independent, accredited GI pathologists. Results: Conclusion: Our study shows that in the pre-EMR cohort, there was an overall prevalence of 15.7% of buried Barrett's and a 14.5% prevalence of buried Barrett's with high grade neoplasia (HGD or IMC). Our results in the post EMR cohort shows an overall prevalence of 33.7% of buried Barrett's with 9.6% prevalence of buried high grade neoplasia (HGD or IMC) suggesting that a third of patients undergoing EMR for Barrett's dysplasia harbour buried Barrett's and a third of these patients harbour high grade neoplasia. This has significant implications for post EMR endoscopic assessment and surveillance. The results from our study shows that there is a need to develop and maintain proficiency in sampling techniques in patients with Barrett's oesophagus. It also shows that the biopsies particularly from those with dysplasia should be carefully reviewed by gastrointestinal pathologists who devote specific attention to identifying buried Barrett's and buried dysplasia. Disclosure of Interest: None Declared